2020
DOI: 10.1002/pssa.202000474
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation and Ni/Cu Plating Approach for Tunnel Oxide Passivated Contacts Solar Cells with Variate Polysilicon Layer Thickness: Gains and Possibilities in Comparison to Screen Printing

Abstract: Recombination of photo-generated charge carriers at metalsemiconductor junctions is a strong limiting factor in achieving high efficiencies for conventional c-Si solar cells [e.g., aluminum back scatter field, passivated emitter rear contact (PERC), etc.]. [1-3] This can be reduced by squeezing the metallized area fraction, but that results in an increase of fill-factor (FF) loses. A novel approach developed at Fraunhofer ISE, namely, tunnel oxide passivated contacts (TOPCon), attempts to counter this effect b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…For screen-printed metallization most of recent publications require a thickness of at least 100 nm of the TOPCon layer to ensure its functionality [4]- [6]. For UV (355 nm) picosecond (ps)-laser ablation before plating the contacts 60-70 nm are sufficient so that the tunneling oxide remains intact as the penetration depth of the laser is around 50-60 nm [3], [7]. Furthermore, contacting these laser contact openings via electroplating of Ni/Cu/Ag would allow an alternative lead-free metallization technique with narrow contact geometries (≤ 25 μm), low contact resistivity ρ c (< 1 mΩcm²) [8] with high throughputs and low cost of ownership (COO) showed by Kluska et al [9].…”
mentioning
confidence: 99%
“…For screen-printed metallization most of recent publications require a thickness of at least 100 nm of the TOPCon layer to ensure its functionality [4]- [6]. For UV (355 nm) picosecond (ps)-laser ablation before plating the contacts 60-70 nm are sufficient so that the tunneling oxide remains intact as the penetration depth of the laser is around 50-60 nm [3], [7]. Furthermore, contacting these laser contact openings via electroplating of Ni/Cu/Ag would allow an alternative lead-free metallization technique with narrow contact geometries (≤ 25 μm), low contact resistivity ρ c (< 1 mΩcm²) [8] with high throughputs and low cost of ownership (COO) showed by Kluska et al [9].…”
mentioning
confidence: 99%
“…[ 21 ] The results of increased recombination are in accordance with observations by Arya et al showing an increase of the contact recombination and that poly‐Si layers below 100 nm remain less sensitive to laser ablation than to screen‐printing metallization. [ 16 ] Further, the analysis of the IV results of the solar cells presented by Arya et al reveal a decrease in V oc and J sc for both metallizations whereby the plated cells feature a higher level. [ 16 ] The expected reduction of the FCA can be seen in the increase of the escape reflection for thinner poly‐Si layers between 1100 and 1200 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Bifacial TOPCon solar cells were manufactured from 156.75 × 156.75 mm 2 large n‐type Cz–silicon wafers featuring a resistivity of 1 Ω cm. The exact processing of the solar cells is discussed in detail in the publication of Arya et al [ 16 ] The schematic cross‐sectional layout is shown in Figure . The produced TOPCon solar cells feature a thermal SiO x layer prepared in a tube furnace and a phosphorus‐doped amorphous silicon (a‐Si) layer deposited in a Centrotherm c.PLASMA tube PECVD with horizontal carrier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second route, low‐temperature metallization pastes could be used for metallization of the rear polylayer, after laser contact opening (LCO) of the rear SiN x :H layer; however, this would require a very tight alignment of laser processing and screen printing, [ 38 ] which would put additional complexity to the process route, possibly with the benefit of reduced J 0,met . Alternatively, the combination of LCO and Ni/Cu plating has shown also very promising for especially very thin n‐doped polysilicon layers [ 39 ] and could be tested for this application.…”
Section: Challengesmentioning
confidence: 99%